Promoting the Synthesis of Precursor Substances by Overexpressing Hexokinase (Hxk) and Hydroxymethylglutaryl-CoA Synthase (Erg13) to Elevate β-Carotene Production in Engineered Yarrowia lipolytica - Qiang, Shan; Wang, Jing; Xiong, Xiao Chao; Qu, Yu Ling; Liu, Liang; Hu, Ching Yuan; Meng, Yong Hong (Frontiers in Microbiology, 2020)
As a valuable carotenoid, β-carotene is commercially used in food, cosmetics, animal feeds, and other industries. Metabolic engineering of microorganisms has been widely explored to improve the production of β-carotene. Compared with the traditional genetic modifications mainly focused on the pathways of mevalonate (MVA) and β-carotene biosynthesis, this study aims to increase the β-carotene production through promoting the synthesis of precursor substances by overexpressing hexokinase and hydroxymethylglutaryl-CoA synthase in an engineered Yarrowia lipolytica. In this study, we investigated the effect of the unique hexokinase gene (Hxk) overexpression on β-carotene accumulation and glucose consumption. The Hxk gene was introduced into a β-carotene producing strain Y.L-1 to generate strain Y.L-2, and this increased the β-carotene content by 98%. Overexpression of the Hxk gene led to increasing in hexokinase activity (329% higher), glucose-6-phosphate content (92% higher), and improvement of the transcriptional level of Hxk (315% higher) compared to the control Y.L-1 strain. Moreover, Hxk overexpression accelerated the utilization rate of glucose. The gene erg13 encoding hydroxymethylglutaryl-CoA synthase was also overexpressed to increase the precursor supply for β-carotene biosynthesis. Recombinant Y.L-4 harboring two copies of erg13 produced 8.41 mg/g dry cell weight (DCW) of β-carotene, which was 259% higher than Y.L-1. The β-carotene content of 9.56 mg/g DCW was achieved in strain Y.L-6 by integrating erg13 into the chromosome and Hxk overexpression. The 3-Hydroxy-3-Methylglutaryl-CoA content in the cells was increased by overexpressing two copies of the erg13 gene. Finally, the titer of β-carotene reached 2.4 g/L using a 50 L bioreactor by the engineered strain, and the fermentation cycle was shortened from 144 h to 120 h. Overall, overexpression of Hxk and erg13 could improve β-carotene production and successfully overcoming the bottleneck of precursor generation to support a more efficient pathway for the production of the target product. Our results revealed a novel strategy to engineer the pathway of β-carotene synthesis.